Mechanism research of catalytic degradation of 1, 2-dichlorobenzene over highly efficient hollow calcium ferrite by in situ FTIR spectra. (June 2022) - Yin, Zhifan; Fan, Shiying; Li, Xinyong; Tadé, Moses O.; Liu, Shaomin
Abstract: The hierarchical CaFe2 O4 core-shell hollow microspheres are successfully fabricated by a facile solvothermal approach following heat treatment process. The hollow architecture exhibits high surface area and strong visible-light absorption capability. Meanwhile, the formation mechanism of hollow structure is proposed based on characterization results. Furthermore, the photocatalytic activity is tested by 1, 2-dichlorobenzene degradation under visible light irradiation, and the degradation ratio of CaFe2 O4 core-shell hollow microspheres can reach 82.0% after 8 h. Moreover, relying on the in situ Fourier transform infrared technology, the catalytic oxidation process and degradation mechanism is clarified on CaFe2 O4 surface, and the intermediate product (formate, acetate, maleate species, etc.) and the mineralized products (CO2 and H2 O) are identified finally. Graphical abstract: Image 1 Highlights: The CaFe2 O4 hierarchical hollow microspheres were fabricated and the mechanisms were explored. Some intermediates and final products were verified by the in situ Fourier transform infrared spectra. The 1, 2-dichlorobenzene conversion ratio over CaFe2 O4 could reach 82.0% after 8 h.